Status gizi, densitas zat gizi, dan keragaman pangan anak balita selama pandemi COVID-19 di Kabupatan Bangli, Bali - Kadek Tresna Adhi; Ni Putu Widarini; Ni Luh Putu Suariyani; Iwan Abdi Suandana; Pande Putu Januraga (Jurnal Gizi Klinik Indonesia, 2022)
Nutritional status, nutrient density, and dietary diversity of children under five during the COVID-19 pandemic in Bangli Regency, BaliBackground: Stunting in children caused the lack of nutritionally balanced food intake in the first two years of life. During the COVID-19 pandemic, the fulfillment of balanced nutrition for children must still be considered to maintain body resistance to avoid COVID-19 infection.Objective: This study was conducted to find out the nutritional status of children and also the knowledge and attitudes of mothers regarding the practice of balanced nutrition based on local food in the COVID-19 pandemic situation. Methods: Cross-sectional study with 202 children aged 23-59 months located in Susut District, Bangli Regency, Bali Province. Data collection includes anthropometric measurements and food recall. Characteristics, knowledge, and attitudes of mothers were conducted by interview using a questionnaire. Results: The nutritional status of subjects showed that the average weight for height z-score (WHZ) was 0.29 ± 1.37, height for age z-score (HAZ) was 0.56 ± 2.38, and weight for age z-score (WAZ) which is -1.18 ± 2.03. The average density of energy intake in the adequate (1.66±0.456), as well as protein density (4.12±0.884 g/100 calories), vitamin B12 (0.225±0.457 mg/100 kcal), and vitamin A (71.7 ±104.6 mg/100 kcal). The majority (61.9%) of subjects consumed less than five food groups in the last 24 hours. The average knowledge of respondents is 69.5±15.3, which is 35.1% in well nutrition knowledge, while most respondent’s attitude has in the good category. Conclusions: Overall children are in normal nutritional status, but it is necessary to attention to the density of vitamins and minerals which are still low, and the lack of food diversity. Suggestion to increase education on balanced nutrition practices based on local food to mothers and families so that they can help grow and also maintain children's health during the COVID-19 pandemic.